Desenvolvimento de revistas didáticas como estratégia lúdica para o ensino da morfofisiologia do sistema endócrino - Silva, Jefferson Lima da (2019)
The teaching of Biology is still seen in classrooms as a traditional teaching in which blackboard and chalk are indispensable, but only this approach tends to entail lack of interest, participation and assimilation of content. Thus, we developed "Hobby" didactic as a facilitator for the teaching of Endocrine System Morphophysiology. This work counted on the participation of the five classes of the second year of high school, totaling 155 students, of wich 80 were female and 75 were male, with ages ranging from 14 to 19 years. The games were developed in pairs of students, after classes on the Endocrine System. 100 games were made, hunting games words (51%), crosswords (18%), labyrinths (15%), forca (13%) and errors (3%). It was observed that the topic most approached by students was the Endocrine System (93%), followed by Endocrine Diseases / Disorders (6%) and Endocrine Disrupters (1%). Finally, it was made by the students /authors by magazine for each class, under the supervision of the teacher. Instead, games developed in a distinct class together with a questionnaire. They can be recognized as the most dynamic, participatory and investigative. The data obtained evidenced the role of the construction of the magazines in the didactic capacity by the student with the same capacity to develop a teacher, logical, low cost and easy applicability, being an instrument that can fill the existing gaps in the literature for the teaching of Morphophysiology of the Endocrine System.